Judging a wine by its bottle : the influence of wine packaging on consumers - Faro, Maria Teresa Ferraz de Andrade de Brito e (2021)
Packaging plays a significant role in the product success, affecting the consumer's purchase intention (Simms & Trott, 2010). For wine, the role of packaging is not different. Wine packaging should be used to turn wine attributes into tangible attributes using visual elements, such as bottle and label shapes, for that purpose (Spawton, 1990). The present research aims to understand how bottle and label shapes influence consumers' quality perception, affect towards wine packaging and, consequently, consumers' purchase intention. To investigate these topics, two different studies were conducted through an online survey with 332 participants. Study I used as stimuli four manipulated bottles, representing different bottle shapes with a traditional label shape (angular). Study II included eight manipulated bottles with different bottle and label shapes. In study I, the results were analysed using structural equation modelling (SEM) and MANOVA, and in the second using a MANOVA. Results show that, for red wine, a high shoulder shape generates a superior quality perception and more favourable affective responses, positively influencing purchase intention, and the same can be concluded for white wine, for a sloping shoulder shape. Involvement and self-confidence were studied but the moderating effects on consumer responses to wine packaging were not confirmed. Regarding the label, angular shapes generate more favourable affective responses than rounded shapes. Moreover, results suggest that label shapes influence consumers’ responses. For an angular shape, findings are similar to the ones obtained in study I in respect to the relationships between bottle shapes and perceived quality and affect. However, a rounded shape distorts these relationships and the bottle shapes no longer have the expected effects. The findings of this research provide useful insights for wine marketers, particularly regarding the guidelines they should follow for the development of effective bottle and label shapes.